A study on workplace violence against healthcare providers in Emergency Department Hospital Tengku Ampuan Rahimah Klang - Jamal, Ahmad Amirin (2018)
Background: Violence towards staffs working in a healthcare facility is a norm, and it is common conversation topics in the news and social media. However, there is not much data that shows the extent of problem, especial in the Malaysian context. This research was done to gauge the frequency of violence towards healthcare providers working in the Emergency Department (ED) of Hospital Tengku Ampuan Rahimah (HTAR) Klang and to see the factors involved. Methodology: A cross sectional prospective study was done in May 2018 among staffs of ED HTAR Klang using a validated Malay language questionnaire. Systematic sampling method was applied. One hundred and sixty completed questionnaires were collected from respondents who were suitable and consented to the questionnaire. The questionnaire collected respondent’s sociodemographic data, their experience, witness or report of workplace violence within 12 months prior to the study. Results: 80.6% of staff had experienced at least one episode of violence within the last 12 months prior to the study, with most of them experiencing verbal abuse (79.4%). A healthcare provider who is married has 3.25 times odds of experiencing workplaceviolence compared to those who are still single and an increase of one month of working experience will increase the odds of having workplace violence by 0.99 times. Conclusion: There was a high prevalence of workplace violence towards healthcare providers working in ED HTAR Klang and if a healthcare provider is married and has less working experience, he or she is more likely to be a victim of workplace violence.